PENGARUH PRODUCT ATRIBUTES DAN CUSTOMER VALUE TERHADAP MINAT BELI KONSUMEN DENGAN PERSEPSI NILAI SEBAGAI VARIABEL MEDIASI PADA PRODUK JADAH DI SELO, BOYOLALI - Afifah, Sarah Dila Nur; Isa, Muzakar (JURNAL LENTERA BISNIS, 2026)
This research aims to analyze the effect of product attributes and customer value on consumers’ purchase intention with perceived value as a mediating variable for jadah products in Selo, Boyolali. A quantitative approach was employed using a survey method involving 322 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that quality value, innovation value, and service value have a significant and positive effect on perceived value, while experience value has no significant effect. Perceived value positively influences purchase intention and significantly mediates the effects of quality value and innovation value on purchase intention. These findings highlight the importance of product quality and innovation in strengthening perceived value and increasing consumers’ purchase intention toward jadah products in Selo.